Obtaining zeros of functions using Python - Pereira, David Lucas (2020)
HNumerical Methods are very important in Engineering because many real problems have complicated mathematical models that are difficult to be solved analytically. Thus, the methods of resolution for several problems that are studied in the discipline of Computational Numerical Methods, as well as in the discipline of Algorithms, are indispensable for the formation of a future Engineer. Among the several numerical methods that exist, the following are the methods for obtaining zeros of functions: Bisection, False Position and Newton-Raphson. The Bisection method consists of defining the range containing a root and, using the arithmetic mean, dividing it until the desired precision is reached. In the case of the False Position method, the weighted arithmetic mean is used to obtain the approximate root. Finally, although Newton-Raphson's method has faster convergence than the others, the drawback of this method is the need to use the derivative of the studied function. Thus, in some cases, this method may be impracticable. In this work, the methods mentioned will be implemented in the Python programming language. In this work, the mentioned methods are implemented in the Python programming language, in order to strengthen programming knowledge in the formation of Engineers, as well as to emphasize the importance of applying numerical methods in practical problems of various engineering areas.